PENGEMBANGAN MODEL PEMBELAJARAN FLIPPED CLASSROOM DENGAN TAKSONOMI BLOOM PADA MATA KULIAH SISTEM POLITIK INDONESIA - Ratna Farida; Amru Alba; Rudi Kurniawan; Zamzami Zainuddin (Balai Besar Guru Penggerak Jawa Timur, 2019)
Traditional learning instruction puts students in a passive learning role such as listening to lectures in the classroom. One of the contemporary innovative instructional approaches is the